Emergence, evolution and mutation: Interpretation of the orderly distribution of pre-modern settlement in the Great Wall zone based on Complex Adaptive System theory - Zhang, Haoyan (International Planning History Society Proceedings, 2018)
The Great Wall zone represents the largest area of land-use and land-cover change in China in the past 300 years, when the borders of agricultural production and settlement continued to move northward, forming the pattern of settlements we see today, realizing its transition from wartime to peacetime. Instead of focusing on the development of individual urban, how can we understand the evolution essence of settlement system, located in the transition zone between agriculture and animal husbandry, from the perspective of complex system? In this article, the distribution pattern can be considered as a spatial projection of region social order. Then, the fractal dimension of settlement distribution is calculated by GIS, so as to demonstrate the complexity of pattern. And then, characteristics and mechanisms of the settlement system in the Great Wall area during Ming and Qing Dynasties is further analyzed from 7 basic points of Complex Adaptive System. Finally, the idea of attracting basin can be used to make a further description about the process of evolution, namely structural break and non-structural evolution.